Development of immobilized systems for enzymatic production of halomonas levan - Yıldırım, Evin Arslan (My University, 2019)
Levan, bir yüzyıldan fazla süredir bilinen ancak son on yılda yenilenen ilgiyi çeken bir fruktan, fruktoz homopolimeridir. Levan, çeşitli sanayi alanlarının özellikle gıda, ilaç, eczane ve tarım gibi farklı uygulamalarıyla ilişkilendirilmiştir, ancak sınırlı mevcudiyeti, ticarileşmesi için ana engel olmuştur. Levan üretimi üzerine çalışan birkaç grubun yanı sıra, Halomonas smyrnensis'in Levan'ı, Halomonas Levan, grubumuzun ilgi odağı olmuştur. Uygun maliyetli levan üretim süreçlerinin geliştirilmesi ile ilgili devam eden araştırmaların bir parçası olarak, bu çalışma, imobilize edilmiş Halomonas levansükraz enzimi ile Halomonas levanın enzimatik üretimine yöneliktir. Bunun için, ilk halofilik rekombinant levansükraz enzimi, rekombinant Escherichia coli hücrelerinden saflaştırılmış ve daha sonra farklı matrislere imobilize edilmiştir. Yüksek tuz konsatrasyonunda levan üretim koşullarının optimize edilmesinin yanısıra levansukraz enziminin stabilitesi ve yeniden kullanılabilirliği çalışılmıştır.

Levan is a fructose homopolymer, a fructan, that has been known for more than a century but has attracted renewed interest within the last decade. Levan has been associated with diverse applications in several industrial fields like mainly food, medicine, pharmacy and agriculture however its limited availability is the main bottleneck for its commercialization. Besides several groups working on levan production, levan by Halomonas smyrnensis, Halomonas levan, has been the focus of interest of our group. As part of ongoing research about the development of cost effective levan production processes, this study aimed at the enzymatic production of Halomonas levan via immobilized Halomonas levansucrase enzyme. For this, first halophilic recombinant levansucrase enzyme was purified from recombinant Escherichia coli cells and then immobilized via different matrices of interest. Optimized conditions for levan production at high salt as well as the reusability and levansucrase enzyme stability were investigated.
Keywords: Bioengineering; Biyomühendislik; Levan; Levansucrase; levansukraz Levan